Mecillinam, a Novel Penicillanic Acid Derivative with Unusual Activity Against Gram-Negative Bacteria - Neu, Harold C. (1976)
The in vitro activity of mecillinam, a 6 β-amidinopenicillanic acid derivative, was investigated. Mecillinam is not active against most gram-positive coccal or bacilliary forms. Many members of the Enterobacteriaceae are inhibited, with 86% of Escherichia coli, 71% of Klebsiella, 62% of Enterobacter, 75% of Salmonella, 69% of Shigella, and 70% of Citrobacter inhibited by 6.3 μg/ml. Indole-positive Proteus and Serratia were generally resistant as are Pseudomonas strains. Although mecillinam is hydrolyzed by gram-negative β-lactamases, the compound inhibits β-lactamase-producing organisms, particularly E. coli. The conductivity of medium used to determine minimal inhibitory concentration and inoculum size produce markedly different values. In medium of high conductivity, 10 mS, mecillinam is inactive against many strains of bacteria. In all media there is a great difference between the minimal inhibitory and minimal bactericidal levels.